Perishield pore filling material as well as preparation method and application thereof
By designing a peri-shield pore filling material including components A and components B, the problem of poor foundation stability in soft soil areas is solved, and the rapid response and high support strength of the material in soft soil areas are achieved, thereby reducing surface settlement.
Patent Information
- Application Number
- CN202411553849.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art lacks specific peri-shield pore filling materials for the formations in soft soil areas, resulting in disasters such as collapse and subsidence in soft soil areas.
Provide a peri-shield pore filling material, including components A and components B, which consists of sodium-based bentonite, calcined kaolin, silicone waterproofing agent, fly ash, building retarder and thickener. The component is an aqueous solution of sodium silicate, and the two are mixed at a volume ratio of 8:1.
This material can react quickly in soft soil areas, has good pumping and viscosity, avoid solid-liquid separation, improve support strength after forming, reduce surface settlement, and improve foundation structure stability.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of shield periphery pore filling materials, and in particular to a shield periphery pore filling material and a preparation method and application thereof. Background Art
[0002] The shield pore filling material can play an important role in the shield tunneling project under important buildings. The shield pore filling material needs to be quickly injected from the inside of the shield to the surrounding of the shield, and can effectively fill and support the shield pores caused by over-excavation of the cutter head, thereby ensuring the stability of the building foundation structure.
[0003] Soft soil refers to a weak saturated clay layer deposited underwater. Soft soil has the characteristics of high compressibility, low strength and poor permeability. Building foundations in soft soil areas are prone to disasters such as collapse and subsidence. Therefore, shield pore filling materials should have higher standards in soft soil areas so that the use of shield pore filling materials to prevent surface subsidence can be maximized. However, in the prior art, no specific shield pore filling material has been proposed for typical strata in soft soil areas.
[0004] In summary, there is an urgent need to study a shield pore filling material for soft soil areas, so as to improve the stability of the building foundation structure and help reduce the occurrence of disasters caused by surface subsidence. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a shield periphery pore filling material and a preparation method and application thereof. The shield periphery pore filling material of the present invention can be suitable for soft soil areas, reducing the occurrence of surface settlement of shield periphery pores in soft soil areas, thereby improving the structural stability of the foundation.
[0006] The present invention provides a shield perimeter pore filling material, the shield perimeter pore filling material comprises component A and component B, the component A comprises sodium-based bentonite, calcined kaolin, organosilicon waterproofing agent, fly ash, building retarder, and thickener; The mass proportions of the sodium bentonite, calcined kaolin, silicone waterproofing agent, fly ash, building retarder and thickener in component A are (25%-28%): (25%-28%): (2%-4%): (2%-3%): (2%-4%): (0.04%-0.08%), respectively, and the balance is water; The B component includes an aqueous solution of sodium silicate.
[0007] Furthermore, the component A also includes silicate cement. By mass, the mass proportions of the sodium bentonite, calcined kaolin, silicone waterproofing agent, fly ash, building retarder, thickener and silicate cement in component A are (25%-28%): (25%-28%): (2%-4%): (2%-3%): (2%-4%): (0.04%-0.08%): (2%-6%), and the balance is water.
[0008] Furthermore, the volume ratio of component A to component B is 8:1.
[0009] Furthermore, the sodium bentonite includes sodium bentonite with a particle size of 350 mesh to 450 mesh.
[0010] Furthermore, the calcined kaolin includes calcined kaolin with a particle size of 300 meshes to 350 meshes.
[0011] Furthermore, the organosilicon waterproofing agent includes SHP-50 organosilicon waterproofing agent.
[0012] Furthermore, the fly ash includes a density of 1.9 g / cm 3 -2.9g / cm 3 of fly ash.
[0013] Furthermore, the building retarder includes sodium pentahydroxycaproate.
[0014] Furthermore, the thickener includes sodium carboxymethyl cellulose.
[0015] Furthermore, the silicate cement includes P.O42.5 type silicate cement.
[0016] Furthermore, the sodium silicate aqueous solution includes a sodium silicate aqueous solution with a modulus of 3.3 and a Baume degree of 38°.
[0017] Furthermore, the shield periphery pore filling material includes component A and component B, wherein component A includes sodium bentonite with a particle size of 350-450 mesh, calcined kaolin with a particle size of 300-350 mesh, an organic silicon waterproofing agent, and a density of 1.9 g / cm 3 -2.9g / cm 3 Fly ash, sodium pentahydroxycaproate, sodium carboxymethyl cellulose, silicate cement; The sodium bentonite with a particle size of 350-450 mesh, the calcined kaolin with a particle size of 300-350 mesh, the organosilicon waterproofing agent, and the density of 1.9 g / cm 3 -2.9g / cm 3The mass proportions of fly ash, sodium pentahydroxycaproate, sodium carboxymethyl cellulose and silicate cement in component A are (25%-28%): (25%-28%): (2%-4%): (2%-3%): (2%-4%): (0.04%-0.08%): (2%-6%), and the balance is water; The B component includes an aqueous solution of sodium silicate having a modulus of 3.3 and a Baume degree of 38°.
[0018] Furthermore, the shield periphery pore filling material includes component A and component B, wherein component A includes sodium bentonite with a particle size of 350-390 mesh, calcined kaolin with a particle size of 300-310 mesh, an organic silicon waterproofing agent, and a density of 1.9 g / cm 3 -2.9g / cm 3 Fly ash, sodium pentahydroxycaproate, sodium carboxymethyl cellulose, silicate cement; The sodium bentonite with a particle size of 350-390 mesh, the calcined kaolin with a particle size of 300-310 mesh, the organosilicon waterproofing agent, and the density of 1.9 g / cm 3 -2.9g / cm 3 The mass proportions of fly ash, sodium pentahydroxycaproate, sodium carboxymethyl cellulose and silicate cement in component A are 25.4%: 25.4%: 3%: 2.5%: 3%: 0.05%: 5.1% respectively, and the balance is water; the added mass ratio of the 350-390 mesh sodium-based bentonite and the calcined kaolin with a particle size of 300-310 mesh is 1:1; The B component includes an aqueous solution of sodium silicate having a modulus of 3.3 and a Baume degree of 38°.
[0019] The present invention also provides a method for preparing the shield periphery pore filling material, the method comprising: S1: Prepare component A: add sodium bentonite, calcined kaolin, silicone waterproofing agent, fly ash, building retarder, and thickener into water and mix them to obtain component A, wherein the mass ratio of sodium bentonite, calcined kaolin, silicone waterproofing agent, fly ash, building retarder, and thickener in component A is (25%-28%): (25%-28%): (2%-4%): (2%-3%): (2%-4%): (0.04%-0.08%), and the balance is water; S2: preparing component B: dissolving sodium silicate in water to obtain a sodium silicate aqueous solution; S3: Component A and component B are mixed at a volume ratio of 8:1 to obtain the shield perimeter pore filling material of the present invention.
[0020] Furthermore, the component A also includes silicate cement. By mass, the mass proportions of the sodium bentonite, calcined kaolin, silicone waterproofing agent, fly ash, building retarder, thickener and silicate cement in component A are (25%-28%): (25%-28%): (2%-4%): (2%-3%): (2%-4%): (0.04%-0.08%): (2%-6%), respectively, and the balance is water.
[0021] The invention also provides application of the shield periphery pore filling material in filling shield periphery pores in soft soil areas.
[0022] The embodiments of the present invention have the following technical effects: 1. The shield perimeter pore filling material of the present invention can be applied to soft soil areas. The shield perimeter pore filling material not only has good pumpability, which is conducive to quickly filling the shield perimeter pores; but also can react quickly and has a certain viscosity, which can avoid the solid-liquid separation of the shield perimeter pore filling material during the reaction process, resulting in a decrease in the supporting strength of the shield perimeter pore filling material after molding.
[0023] 2. In the selection of the shield periphery pore filling material of the present invention, it is necessary not only to consider the parameters such as the viscosity of the shield periphery pore filling material, so that the shield periphery pore filling material has pumpability and can be smoothly pumped into the shield periphery pore, but also to further consider the composition and proportion of component A and component B, so that the shield periphery pore filling material can improve the reaction speed of the shield periphery pore filling material and the support strength after reaction molding on the basis of having pumpability; In the present invention, sodium bentonite and calcined kaolin contain silicate and aluminate, and silicate cement contains silicate, so it will react with silicate ions in sodium silicate aqueous solution to form a gel, which is beneficial to increase the strength of the slurry after molding, and is the main source of the supporting strength of the pore filling material around the molding, which is beneficial to reduce the surface decline in soft soil areas; and fly ash is a lightweight filler. In the process of sodium bentonite, calcined kaolin, silicate cement and sodium silicate aqueous solution reacting, fly ash can fill the gaps in the paste after slurry molding, which is beneficial to improve the paste's chamber tightness; the porous structure of fly ash can act as a lubricant during pumping, improve pumpability, and reduce the occurrence of blockage and other situations caused by slurry; fly ash can also reduce the hydration heat of slurry, and reduce the situation of cracks in the paste after molding caused by temperature changes during the reaction. In addition, fly ash can also cooperate with organic silicon waterproofing agents to not only reduce the absorption of external moisture by the slurry during the reaction, but also reduce the occurrence of solid-liquid separation in the slurry, which is beneficial to the speed and effect of the reaction. On this basis, the building retarder in the slurry is adsorbed on the surface of the silicate cement, delaying the hydration reaction, thereby ensuring that it will not react and form during the pumping process, while the thickener can increase the viscosity of the slurry, thereby ensuring the pumpability of the slurry during the pumping process and further reducing pipe blockage.
[0024] 3. The method of the present invention is simple, easy to implement, and can be used for industrial production. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0026] In a first aspect, some embodiments of the present invention provide a shield perimeter pore filling material, the shield perimeter pore filling material comprising component A and component B, the component A comprising sodium bentonite, calcined kaolin, organosilicon waterproofing agent, fly ash, building retarder, and thickener; The mass proportions of the sodium bentonite, calcined kaolin, silicone waterproofing agent, fly ash, building retarder and thickener in component A are (25%-28%): (25%-28%): (2%-4%): (2%-3%): (2%-4%): (0.04%-0.08%), respectively, and the balance is water; The B component includes an aqueous solution of sodium silicate.
[0027] Furthermore, the component A also includes silicate cement. By mass, the mass proportions of the sodium bentonite, calcined kaolin, silicone waterproofing agent, fly ash, building retarder, thickener and silicate cement in component A are (25%-28%): (25%-28%): (2%-4%): (2%-3%): (2%-4%): (0.04%-0.08%): (2%-6%), respectively, and the balance is water.
[0028] In the present invention, the sodium base can improve the expansibility of bentonite, which is conducive to fixing the moisture in component A and preventing solid-liquid separation. The calcined kaolin has better thermal and acid-alkali resistance. The reaction speed of the silicate and aluminate in sodium-based bentonite and calcined kaolin with the sodium silicate aqueous solution in component B can be effectively improved, and the shield pore filling material also has acid and alkali resistance after molding. Adding a mass fraction of 2%-6% of silicate cement to component A can further improve the support strength after molding on the one hand, avoid the harm caused by sinking, and on the other hand reduce the hydration heat generated by cement. The selection of fly ash addition quality needs to consider not only reducing the hydration heat, but also improving the freeze-thaw durability of the slurry, reducing the strength reduction of the shield pore filling material after molding due to poor frost resistance or excessive hydration heat. Therefore, the appropriate addition quality can improve the strength of the shield pore filling material after molding, thereby playing a role in controlling settlement. The addition quality of fly ash is 2%-3%. When adding 2%-4% of organosilicon waterproofing agent and building retarder to form an effective paste during the slurry reaction, the water reduction effect caused by excessive addition of organosilicon waterproofing agent and building retarder is avoided, and the strength of the paste after molding is guaranteed. Sodium bentonite, calcined kaolin, and silicate cement all contain silicates. Organosilicon waterproofing agents are conducive to being adsorbed on the surface of materials, which can enhance the ability to prevent water penetration and reduce solid-liquid separation caused by water penetration in the slurry.
[0029] In some embodiments, the volume ratio of component A to component B is 8:1.
[0030] The volume ratio of component A to component B is 8:1, which is not only conducive to the rapidity and completeness of the reaction, but also ensures that the strength of the shield perimeter pore filling material after molding is optimal.
[0031] In some embodiments, the sodium bentonite comprises sodium bentonite having a particle size of 350-450 mesh.
[0032] In some embodiments, the calcined kaolin comprises calcined kaolin with a particle size of 300-350 meshes.
[0033] The appropriate particle size can not only ensure the dispersibility in the slurry, but also will not have too much impact on the fluidity of the slurry. Therefore, the particle size of the sodium bentonite in the present invention is selected to be between 350 mesh and 450 mesh, and the particle size of the calcined kaolin is selected to be between 300 mesh and 350 mesh.
[0034] In some embodiments, the organosilicon waterproofing agent includes SHP-50 organosilicon waterproofing agent.
[0035] In some embodiments, the fly ash comprises a density of 1.9 g / cm 3 -2.9g / cm 3 of fly ash.
[0036] Density: 1.9 g / cm 3 -2.9g / cm 3 The fly ash can increase the volume of the slurry, fill the gaps between aggregates, improve the fluidity and pumpability of the slurry, and at the same time reduce the water seepage phenomenon of the freshly mixed slurry, reduce the hydration heat of the slurry, and reduce cracks caused by temperature changes.
[0037] In some embodiments, the building retarder includes sodium pentahydroxycaproate.
[0038] In some embodiments, the thickener comprises sodium carboxymethyl cellulose.
[0039] Sodium carboxymethyl cellulose is a linear high molecular weight ionic cellulose ether, whose molecular chain can absorb water molecules to form a hydration layer. At the same time, the sodium carboxymethyl cellulose molecules interact with each other to form a three-dimensional network structure, so that sodium bentonite, calcined kaolin, silicate cement, etc. can be evenly distributed in the slurry, thus ensuring the performance of the slurry.
[0040] In some embodiments, the silicate cement includes P.O42.5 type silicate cement.
[0041] In some embodiments, the sodium silicate aqueous solution includes a sodium silicate aqueous solution having a modulus of 3.3 and a Baume degree of 38°.
[0042] In the present invention, the preparation of sodium silicate is obtained by the reaction between silicon dioxide and sodium oxide, and sodium silicate with different moduli can be obtained by adjusting the addition amount between silicon dioxide and sodium oxide. Baume represents the mass concentration of sodium silicate aqueous solution. In component B, in order to obtain a sodium silicate solution with suitable viscosity, not only the modulus of sodium silicate is set, but also the Baume degree of the sodium silicate aqueous solution is further set. What is used in the present invention is a sodium silicate aqueous solution with a modulus of 3.3 and a Baume degree of 38°, which has a higher viscosity, is not only conducive to the stability of the aqueous solution, but also conducive to improving the adhesion between the materials with the substances of component A during the reaction process, and realizing the stability and reinforcement of the foundation.
[0043] In some embodiments, the shield perimeter pore filling material includes component A and component B, wherein component A includes sodium bentonite with a particle size of 350-450 mesh, calcined kaolin with a particle size of 300-350 mesh, an organic silicon waterproofing agent, and a density of 1.9 g / cm 3 -2.9g / cm 3 Fly ash, sodium pentahydroxycaproate, sodium carboxymethyl cellulose, silicate cement; The sodium bentonite with a particle size of 350-450 mesh, the calcined kaolin with a particle size of 300-350 mesh, the organosilicon waterproofing agent, and the density of 1.9 g / cm 3 -2.9g / cm 3 The mass proportions of fly ash, sodium pentahydroxycaproate, sodium carboxymethyl cellulose and silicate cement in component A are (25%-28%): (25%-28%): (2%-4%): (2%-3%): (2%-4%): (0.04%-0.08%): (2%-6%), and the balance is water; The B component includes an aqueous solution of sodium silicate having a modulus of 3.3 and a Baume degree of 38°.
[0044] In the present invention, by designing the volume morphology of sodium bentonite, calcined kaolin and fly ash, the gaps formed between the particles can be fully filled, thereby facilitating the strength of the shield pore filling material after molding. The viscosity and concentration of the sodium silicate aqueous solution are designed to be beneficial to the stability of the B component before it reacts, and to the sufficient contact between the A component and the B component during the reaction, thereby increasing the reaction speed.
[0045] In some embodiments, the shield perimeter pore filling material includes component A and component B, wherein component A includes sodium bentonite with a particle size of 350-390 mesh, calcined kaolin with a particle size of 300-310 mesh, an organic silicon waterproofing agent, and a density of 1.9 g / cm 3 -2.9g / cm 3Fly ash, sodium pentahydroxycaproate, sodium carboxymethyl cellulose, silicate cement; The sodium bentonite with a particle size of 350-390 mesh, the calcined kaolin with a particle size of 300-310 mesh, the organosilicon waterproofing agent, and the density of 1.9 g / cm 3 -2.9g / cm 3 The mass proportions of fly ash, sodium pentahydroxycaproate, sodium carboxymethyl cellulose and silicate cement in component A are 25.4%: 25.4%: 3%: 2.5%: 3%: 0.05%: 5.1% respectively, and the balance is water; the added mass ratio of the 350-390 mesh sodium-based bentonite and the calcined kaolin with a particle size of 300-310 mesh is 1:1; The B component includes an aqueous solution of sodium silicate having a modulus of 3.3 and a Baume degree of 38°.
[0046] In a second aspect, some embodiments provide a method for preparing the shield peripore filling material, the preparation method comprising: S1: Prepare component A: add sodium bentonite, calcined kaolin, silicone waterproofing agent, fly ash, building retarder, and thickener and mix them in water to obtain component A, wherein the mass ratio of sodium bentonite, calcined kaolin, silicone waterproofing agent, fly ash, building retarder, and thickener is (25%-28%): (25%-28%): (2%-4%): (2%-3%): (2%-4%): (0.04%-0.08%), and the balance is water; S2: preparing component B: dissolving sodium silicate in water to obtain a sodium silicate aqueous solution; S3: Component A and component B are mixed at a volume ratio of 8:1 to obtain the shield perimeter pore filling material of the present invention.
[0047] In some embodiments, the component A also includes silicate cement. By mass, the sodium bentonite, calcined kaolin, silicone waterproofing agent, fly ash, building retarder, thickener, and silicate cement in component A account for (25%-28%): (25%-28%): (2%-4%): (2%-3%): (2%-4%): (0.04%-0.08%): (2%-6%), respectively, and the remainder is water.
[0048] The shield perimeter pore filling material is divided into component A and component B for separate preparation. The first aspect is to prevent premature mixing, which leads to early reaction and is not conducive to the pumping process. In the present invention, sodium-based bentonite, calcined kaolin and sodium silicate aqueous solution react to form a paste, which is the basis of the strength of the entire paste. Therefore, it needs to be divided into component A and component B, and the silicate cement added to component A is used to further improve the strength. In order to reduce the premature reaction of silicate cement with component B, component A is added. Fly ash and thickener can further adjust the fluidity and viscosity of the slurry. Building retarders are adsorbed on the surface of silicate cement to delay the hydration reaction. The organosilicon waterproofing agent is to ensure that solid-liquid separation is avoided in the slurry of component A, resulting in poor uniformity, and to avoid insufficient reaction with component B, resulting in a decrease in the strength of the shield perimeter pore filling material after molding. Based on the above reasons, the shield perimeter pore filling material is divided into component A and component B for preparation, and the two are mixed when they need to be pumped.
[0049] In a third aspect, some embodiments provide the use of the shield perimeter pore filling material in filling the shield perimeter pores in soft soil areas.
[0050] The following is further described in conjunction with specific embodiments.
[0051] Embodiment 1: The shield periphery pore filling material of this embodiment comprises liquid A and liquid B. Liquid A comprises 26% by weight of 370-mesh sodium bentonite and 325-mesh calcined kaolin, 3.1% by weight of SHP-50 organosilicon waterproofing agent, and 2.6% by weight of 1.9 g / cm 3 -2.9g / cm 3 It is a mixture of fly ash, 3.1% by mass of sodium pentahydroxycaproate, 2.6% by mass of P.O42.5 silicate cement, 0.05% by mass of thickener sodium carboxymethyl cellulose, and the remainder is water; liquid B is an aqueous solution of sodium silicate with a modulus of 3.3 and a Baume degree of 38°; the volume ratio of liquid A to liquid B is 8:1.
[0052] Example 2 The difference between the shield perimeter pore filling material of this embodiment and that of embodiment 1 is that the mass proportion of 400-mesh sodium-based bentonite and 325-mesh calcined kaolin in liquid A of this embodiment is 27.6%, the mass proportion of SHP-50 type silicone waterproofing agent is 3.0%, and the mass proportion of 1.9 g / cm 3 -2.9g / cm 3 The mass proportion of fly ash is 2.5%, the mass proportion of sodium pentahydroxycaproate is 3.0%, the mass proportion of thickener sodium carboxymethyl cellulose is 0.08%, the mass proportion of P.O42.5 silicate cement is 3.8%, and the balance is water. Other contents are the same as those in Example 1.
[0053] Example 3 The difference between the shield perimeter pore filling material of this embodiment and that of embodiment 1 is that the mass proportion of 400 mesh sodium-based bentonite and 325 mesh calcined kaolin in liquid A is 26.3%, the mass proportion of SHP-50 type silicone waterproofing agent is 3.0%, and the mass proportion of 1.9 g / cm 3 -2.9g / cm 3 The mass proportion of fly ash is 2.5%, the mass proportion of sodium pentahydroxycaproate is 3.0%, the mass proportion of thickener sodium carboxymethyl cellulose is 0.08%, the mass proportion of P.O42.5 silicate cement is 4.3%, and the balance is water. Other contents are the same as those in Example 1.
[0054] Example 4 The difference between the shield perimeter pore filling material of this embodiment and that of embodiment 1 is that the mass proportion of 400-mesh sodium-based bentonite and 325-mesh calcined kaolin in liquid A is 25.4%, the mass proportion of SHP-50 type silicone waterproofing agent is 3.0%, and the mass proportion of 1.9 g / cm 3 -2.9g / cm 3 The mass proportion of fly ash is 2.5%, the mass proportion of sodium pentahydroxycaproate is 3.0%, the mass proportion of thickener sodium carboxymethyl cellulose is 0.05%, the mass proportion of P.O42.5 silicate cement is 5.1%, and the balance is water. Other contents are the same as those in Example 1.
[0055] Embodiment 5: The difference between Example 5 and Example 4 is that the sodium bentonite is 370 mesh, the calcined kaolin is 310 mesh, and the rest is the same as Example 4.
[0056] In Comparative Examples 1 to 4: The shield pore filling materials in Comparative Examples 1 to 4 include liquid A and liquid B. The bentonite in liquid A is 400 mesh sodium-based bentonite, and the fly ash is 1.9 g / cm 3 -2.9g / cm 3 Fly ash, SHP-50 silicone waterproofing agent, sodium pentahydroxycaproate retarder, sodium carboxymethyl cellulose thickener, P.O42.5 silicate cement. Liquid B is a sodium silicate aqueous solution with a modulus of 3.3 and a Baume degree of 38°.
[0057] Comparative Example 5: The added mass ratio of sodium bentonite to calcined kaolin is 4:1, the added mass of sodium bentonite in component A is 35%, the thickeners are sodium carboxymethyl cellulose and polyacrylamide, the mass ratio of sodium carboxymethyl cellulose to polyacrylamide is 1:1.1, and other parameters are the same as in Example 1.
[0058] The shield periphery pore filling materials in the above-mentioned embodiments and comparative examples were tested, and the test results are shown in Table 1 and Table 2: Results and Analysis Table 1 Effects of slurries of Comparative Examples 1 to 4
[0059] A:B represents the volume ratio of liquid A to liquid B.
[0060] Table 2 Performance test results of shield perimeter pore filling materials of Examples 1 to 4
[0061] The shield periphery pore filling materials of the present invention cooperate with each other, so that the shield periphery pore filling materials can react quickly, support the foundation in soft soil areas, reduce surface settlement of shield periphery pores in soft soil areas, and thus improve the structural stability of the foundation. In Table 1, it can be found in Comparative Example 1 that when the amount of cement is too much, the slurry after molding will be too hard, and the hydration heat will also increase, causing cracking and the like, and no calcined kaolin is added in Comparative Example 1. Calcined kaolin can replace part of the cement dosage, thereby reducing the hydration heat and reducing the problems caused by the slurry being too hard. It can be further verified in Comparative Examples 2-4 that when the components and proportions of the designed A liquid and B liquid are not appropriate, the effect of obtaining the mixed slurry will be poor, and the expected effect cannot be achieved. It can be seen that the pumping slurry of the embodiment of the present invention, because of the interaction between the components in liquid A and liquid B, and the addition relationship between the components and between liquid A and liquid B is further designed, finally a slurry that can reduce the surface settlement of the shield pores in soft soil areas is obtained. It can be verified by Table 2. In Table 2, the shield pore filling materials obtained in Examples 1 to 4 all have good viscosity, water retention rate and cross-plate shear strength (cross-plate shear strength represents the torque resistance and shear strength of the paste after molding), which can achieve strong support strength for the shield pores in soft soil areas and reduce surface subsidence. For typical clay and silt soil in soft soil areas, the water content of the formation is high and the formation deformation develops rapidly. Among them, Example 4 has the best effect. The shield pore filling material of Example 4 has a certain viscosity and water retention rate. At the same time, its cross-plate shear strength is high, which can improve the anti-sinking ability of the shield gap filling material, and has a more positive effect on inhibiting formation settlement. At the same time, each ratio index can meet the requirements of engineering use.
[0062] On this basis, further study was conducted on Example 4 and Example 5, and it was found that the viscosity and cross-plate shear strength of Example 5 increased compared with Example 4 because Example 5 had a more suitable particle size than Example 4, which increased the specific surface area of sodium bentonite and calcined kaolin in the slurry, thereby facilitating the improvement of the viscosity of the slurry, avoiding solid-liquid separation, and thus the paste after molding had stronger supporting strength. Further preferred are 350-390 mesh sodium bentonite and 300-310 mesh calcined kaolin.
[0063] Finally, in the current technology, polyacrylamide in Comparative Example 1 is often used as a thickener in the slurry. Polyacrylamide can promote rapid fusion with water glass, so that the reaction occurs quickly, and polyacrylamide is often compounded with sodium carboxymethyl cellulose to increase the viscosity of the slurry. However, due to the properties of polyacrylamide, polyacrylamide is often used as a pore filling material in non-soft soil areas. In the soft soil area, in order to promote the slurry in the pores to fill the pores fully, on the one hand, it is necessary to control the viscosity of the slurry so that the slurry can be fully filled into each pore. On the other hand, the soft soil area has rheology and thixotropy. The slurry filled in the soft soil is often more than the volume of the pores, which is conducive to improving the rheology and thixotropy of the soft soil area, thereby improving the supporting strength of the paste in the pores of the soft soil area. The slurry with polyacrylamide reacts too fast, which makes it impossible to fully fill the pores, resulting in less improvement of the pores in the soft soil area by the slurry. In Example 5 of the present invention, the viscosity of the slurry is controlled by controlling the particle size of sodium bentonite and calcined kaolin. On this basis, by adding calcined kaolin of the same mass as sodium bentonite, firstly, part of the cement is replaced, thereby reducing the hydration heat on the basis of improving the supporting strength of the paste. Secondly, the number of calcined bentonite and sodium bentonite particles is equivalent, so polyacrylamide can be avoided, and the reaction rate of liquid A and liquid B can be controlled, so that the slurry can be fully filled in the soft soil area.
[0064] In summary, the shield periphery pore filling materials obtained by the present invention cooperate with each other, so that the shield periphery pore filling materials can react quickly, achieve a supporting effect on the foundation in the soft soil area, reduce the surface settlement of the shield periphery pores in the soft soil area, and thus improve the structural stability of the foundation.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the technical solutions of the embodiments of the present invention.
Claims
1. A shield perimeter pore filling material, characterized in that: The shield perimeter pore filling material comprises component A and component B, wherein component A comprises sodium bentonite, calcined kaolin, organosilicon waterproofing agent, fly ash, building retarder, and thickener; The mass proportions of the sodium bentonite, calcined kaolin, silicone waterproofing agent, fly ash, building retarder and thickener in component A are (25%-28%): (25%-28%): (2%-4%): (2%-3%): (2%-4%): (0.04%-0.08%), respectively, and the balance is water; The B component includes an aqueous solution of sodium silicate.
2. The shield perimeter pore filling material according to claim 1, characterized in that: The volume ratio of the A component to the B component is 8:
1.
3. The shield perimeter pore filling material according to claim 1, characterized in that: The component A also includes silicate cement. By mass, the sodium bentonite, calcined kaolin, silicone waterproofing agent, fly ash, building retarder, thickener and silicate cement in component A account for (25%-28%): (25%-28%): (2%-4%): (2%-3%): (2%-4%): (0.04%-0.08%): (2%-6%), respectively, and the balance is water.
4. The shield perimeter pore filling material according to claim 1, characterized in that: The sodium bentonite includes sodium bentonite with a particle size of 350 mesh to 450 mesh; The calcined kaolin comprises calcined kaolin with a particle size of 300 meshes to 350 meshes; The organosilicon waterproofing agent includes SHP-50 organosilicon waterproofing agent; The fly ash comprises a density of 1.9 g / cm 3 -2.9g / cm 3 of fly ash; The building retarder includes sodium pentahydroxycaproate; The thickener includes sodium carboxymethyl cellulose; The silicate cement includes P.O42.5 type silicate cement.
5. The shield perimeter pore filling material according to claim 1, characterized in that: The sodium silicate aqueous solution includes a sodium silicate aqueous solution having a modulus of 3.3 and a Baume degree of 38°.
6. The shield perimeter pore filling material according to claim 1, characterized in that: The shield perimeter pore filling material comprises component A and component B, wherein component A comprises sodium bentonite with a particle size of 350-450 mesh, calcined kaolin with a particle size of 300-350 mesh, an organic silicon waterproofing agent, and a density of 1.9 g / cm 3 -2.9g / cm 3 Fly ash, sodium pentahydroxycaproate, sodium carboxymethyl cellulose, silicate cement; The sodium bentonite with a particle size of 350-450 mesh, the calcined kaolin with a particle size of 300-350 mesh, the organosilicon waterproofing agent, and the density of 1.9 g / cm 3 -2.9g / cm 3 The mass proportions of fly ash, sodium pentahydroxycaproate, sodium carboxymethyl cellulose and silicate cement in component A are (25%-28%): (25%-28%): (2%-4%): (2%-3%): (2%-4%): (0.04%-0.08%): (2%-6%), and the balance is water; The B component includes an aqueous solution of sodium silicate having a modulus of 3.3 and a Baume degree of 38°.
7. The shield perimeter pore filling material according to claim 1, characterized in that: The shield perimeter pore filling material comprises component A and component B, wherein component A comprises sodium bentonite with a particle size of 350-390 mesh, calcined kaolin with a particle size of 300-310 mesh, an organosilicon waterproofing agent, and a density of 1.9 g / cm 3 -2.9g / cm 3 Fly ash, sodium pentahydroxycaproate, sodium carboxymethyl cellulose, silicate cement; The sodium bentonite with a particle size of 350-390 mesh, the calcined kaolin with a particle size of 300-310 mesh, the organosilicon waterproofing agent, and the density of 1.9 g / cm 3 -2.9g / cm 3 The mass proportions of fly ash, sodium pentahydroxycaproate, sodium carboxymethyl cellulose and silicate cement in component A are 25.4%: 25.4%: 3%: 2.5%: 3%: 0.05%: 5.1% respectively, and the balance is water; the added mass ratio of the 350-390 mesh sodium-based bentonite and the calcined kaolin with a particle size of 300-310 mesh is 1:1; The B component includes an aqueous solution of sodium silicate having a modulus of 3.3 and a Baume degree of 38°.
8. A method for preparing a shield perimeter pore filling material according to any one of claims 1 to 7, the method comprising: S1: Prepare component A: add sodium bentonite, calcined kaolin, silicone waterproofing agent, fly ash, building retarder, and thickener and mix them in water to obtain component A, wherein the mass ratio of sodium bentonite, calcined kaolin, silicone waterproofing agent, fly ash, building retarder, and thickener is (25%-28%): (25%-28%): (2%-4%): (2%-3%): (2%-4%): (0.04%-0.08%), and the balance is water; S2: preparing component B: dissolving sodium silicate in water to obtain a sodium silicate aqueous solution; S3: Component A and component B are mixed at a volume ratio of 8:1 to obtain the shield perimeter pore filling material of the present invention.
9. The preparation method according to claim 8, characterized in that: The component A also includes silicate cement. By mass, the sodium bentonite, calcined kaolin, silicone waterproofing agent, fly ash, building retarder, thickener and silicate cement in component A account for (25%-28%): (25%-28%): (2%-4%): (2%-3%): (2%-4%): (0.04%-0.08%): (2%-6%), respectively, and the balance is water.
10. Use of the shield perimeter pore filling material according to any one of claims 1 to 7 in filling shield perimeter pores in soft soil areas.